FACTORS CONTRIBUTE TO MARITAL PROBLEMS AMONG MALAY MUSLIM WOMEN: A CASE STUDY IN MALAYSIA - Azahari, Raihanah (Jurnal Syariah, 2008)
Conflict in marriage is part of the process that helps couples to be more mature in their marital life. However, it tends to be the source of marital breakdown if not dealt with wisely. In many situations, women are always victims to this break up.This paper will analyze the types of marital problems which had been faced by Muslim Malay women. Files of family cases at the Counselling Unit of the State Islamic Religion Departments had been referred to obtain the data particularly the demographic background of couples and also the information regarding the problems that lead them to the Counselling Unit. This research which had been carried out in three states identified more than 40 types of cases that had been reported by women.